Competency-Based Education: Purposes and Promises - Walden, Patrick R. (Seminars in Speech and Language, 2020)
Competency-based education (CBE) is described and the reported advantages to CBE are discussed. The need for a stronger evidence base to support CBE is acknowledged. As we continue to develop this evidence base, the practices of (1) focusing on outcomes and (2) being flexible in the time needed for trainee mastery of competencies hold promise and are consistent with good pedagogy. A model for clinical supervision that includes a focus on outcomes, as well as built-in acknowledgment of time for mastery, is briefly described.
Keywords: competency-based education; speech-language pathology; audiology; higher education; clinical supervision